GheOP3S tool and START/STOPP criteria version 2 for screening of potentially inappropriate medications and omissions in nursing home residents. Issue 1 (5th February 2019) - Stojanović, Marko; Vuković, Milica; Jovanović, Milan; Dimitrijević, Srđan; Radenković, Miroslav
Abstract: Rationale, aims, and objective: There is limited information about the comparative effectiveness of the START/STOPP (Screening Tool of Older Person's Prescriptions/Screening Tool to Alert doctors to Right Treatment) criteria and the Ghent Older People's Prescriptions community Pharmacy Screening tool (GheOP 3 S tool) for the screening of potentially inappropriate prescribing (PIP) in the geriatric population. Considering this, the aim of this study was to compare the ability of the START/STOPP criteria and GheOP 3 S tool to identify the PIP and potential prescribing omissions (PPOs) among elderly patients visiting their primary care physician. Methods: This is a retrospective observational study where a total of 422 subjects were included. The Charlson Co‐morbidity Index (CCI) and the Medicines Co‐morbidity Index (MCI) for older people were used to determine the co‐morbidity status. The user's diagnosis and medications prescribed were analysed with the START/STOPP criteria and GheOP 3 S tool. The Wilcoxon signed rank test was used to compare these criteria. The statistical relationship between the occurrence of PIP and users' age, the number of medication prescribed, the number of diagnoses, CCI, and MCI was determined with one‐tailed bivariate correlation. Results: The START/STOPP criteria detected 843 PIPs and 1067 PPOs, while the GheOP 3 S tool detected 936 PIPs and 202 PPOs. The GheOP 3 S tool detected significantly more PIPs than did the STOPP criteria ( P = 0.003). A significantly higher number of PPOs were detected with the START criterion ( P < 0.0001). The results obtained with the START/STOPP criteria positively correlated with mentioned variables. Oppositely, there is a negative correlation between the results obtained with the GheOP 3 S tool and age. Still, the positive correlation could be found with the rest of the variables. Conclusion: The results of this study indicate that both tested tools demonstrated efficiency to detect PIPs and PPOs. The GheOP 3 S tool detected significantly more PIPs than did the STOPP criteria. On the other hand, the START criteria performed much better for the screening of PPOs.